The impact of diabetic foot syndrome on quality of life - Stanisławska, Joanna; Talarska, Dorota; Matczyńska, Katarzyna; Drozd-Gajdus, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Background. Diabetes is a chronic disease leads to numerous restrictions in patient functioning. The need for continuous therapy and medical supervision as well as various complications exert a negative influence on the quality of life in this group of patients. Aim. Evaluation of the functioning and quality of life of patients with diabetic foot syndrome (DF). Material and methods. The study included 100 randomly selected patients with a mean age of 61.5 ± 11.4 years, of both sexes (30% of women and 70% men) with diabetic foot syndrome. To assess the degree of functioning scale was used Barthel and Karnofsky scale activity. Quality of life was measured using the WHOQOL-BREF scale. Results. In the assessment of functional capacity in 57% patients had a light condition. In 43% patients were diagnosed with the condition medium duty, requiring the help of others. The Karnofsky’ 33% of respondents identified their condition as good with preserving the independence of its most self-service operations. 5% of patients require constant care. Overall assessment of the quality of life of the subjects in the study DF I was worse (mean 3.1 ± 0.9) than in study II (mean 3.3 ± 0.8). Conclusions. Patients with DF have worse functional abilities, even men with DF function better in their daily lives than women. Quality of life is different from the time taken testing and treatment. It was also shown that the better the quality of life in environmental and social functioning, and worse physical and mental.